Highly public anti-Black violence and preterm birth odds for Black and White mothers - David S. Curtis; Ken R. Smith; David H. Chae; Tessa Washburn; Hedwig Lee; Jaewhan Kim; Michael R. Kramer (Elsevier, 2022)
Highly public anti-Black violence may increase preterm birth in the general population of pregnant women via stress-mediated paths, particularly Black women exposed in early gestation. To examine spillover from racial violence in the US, we included a total of 49 high publicity incidents of the following types: police lethal force toward Black persons, legal decisions not to indict/convict officers involved, and hate crime murders of Black victims. National search interest in these incidents was measured via Google Trends to proxy for public awareness of racial violence. Timing of racial violence was coded in relation to a three-month preconception period and subsequent pregnancy trimesters, with the primary hypothesis being that first trimester exposure is associated with higher preterm birth odds. The national sample included 1.6 million singleton live births to US-born Black mothers and 6.6 million births to US-born White mothers from 2014 to 2017. Using a preregistered analysis plan, findings show that Black mothers had 5% higher preterm birth odds when exposed to any high publicity racial incidents relative to none in their first trimester, and 2-3% higher preterm birth odds with each log10 increase in national interest. However, post hoc sensitivity tests that included month fixed effects attenuated these associations to null. For White mothers, associations were smaller but of a similar pattern, and were attenuated when including month fixed effects. Highly public anti-Black violence may act as a national stressor, yet whether racial violence is associated with reproductive outcomes in the population is unknown and merits further research.